2017
DOI: 10.3389/fmars.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Philopatry and Regional Connectivity of the Great Hammerhead Shark, Sphyrna mokarran in the U.S. and Bahamas

Abstract: A thorough understanding of movement patterns of a species is critical for designing effective conservation and management initiatives. However, generating such information for large marine vertebrates is challenging, as they typically move over long distances, live in concealing environments, are logistically difficult to capture and, as uppertrophic predators, are naturally low in abundance. Large-bodied, broadly distributed tropical shark typically restricted to coastal and shelf habitats, the great hammerh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 69 publications
8
70
0
Order By: Relevance
“…Great hammerheads are one of the largest-bodied species of predatory sharks [20] and can travel long distances over short periods of time [24], including movements exceeding 1500 km [9]. Acknowledging our relatively short tracking periods, two of the three great hammerheads tagged in this study showed movement less than 35 km between tagging and pop-off locations.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Great hammerheads are one of the largest-bodied species of predatory sharks [20] and can travel long distances over short periods of time [24], including movements exceeding 1500 km [9]. Acknowledging our relatively short tracking periods, two of the three great hammerheads tagged in this study showed movement less than 35 km between tagging and pop-off locations.…”
Section: Discussionmentioning
confidence: 77%
“…Using a combination of techniques, Guttridge et al [9] identified large-scale migrations, seasonal residency, and site fidelity in great hammerheads tracked in Florida and the Bahamas. Similarly, Graham et al [10] identified areas of core habitat use in relationship to marine protected areas along the coast of Florida and the Bahamas, but noted that their findings may not be representative of the entire population.…”
Section: Open Accessmentioning
confidence: 99%
“…This method is only applicable across vertical habitats exhibiting a temperature profile that monotonically and continuously varies with depth, and is not appropriate in locations without considerable temperature gradients, such as the nearly constant depth-versus-temperature profile of the Mediterranean Sea in the winter [28,46]. Furthermore, this technique is applicable to animals that traverse through the temperature gradients of the water column and, therefore, may not be suitable for benthic or vertically stationary species [47], or species that may follow isotherms (e.g., great hammerhead sharks, Sphyrna mokarran) [48]. We recommend using the CCF to compare similar datasets, such as data from multiple conspecifics at the same study site.…”
Section: Discussionmentioning
confidence: 99%
“…The continued exploitation of highly migratory species has implications for the economy of several Bahamian Family Islands. In particular, “rare‐species” dives that focus on interactions with highly migratory charismatic species in specific locations at specific times of year are at risk: for example, oceanic whitetip shark, Carcharhinus longimanus (Poey), dives in southern Cat Island (Howey‐Jordan et al., ), great hammerhead shark, Sphyrna mokarran (Rüppell), dives in South Bimini (Guttridge et al., ) and tiger shark dives in West End, Grand Bahama (Hammerschlag, Gutowsky, Gallagher, Matich, & Cooke, ). Despite rare‐species dives only generating ~18% of the revenue of shark–dive tourism in The Bahamas, the importance of this income is greater in economically depauperate Family Islands where these interactions take place.…”
Section: Achievements In Species Conservationmentioning
confidence: 99%
“…Carcharhinus longimanus (Poey), dives in southern Cat Island(Howey-Jordan et al, 2013), great hammerhead shark, Sphyrna mokarran (Rüppell), dives in South Bimini(Guttridge et al, 2017) and tiger shark dives in West End, Grand Bahama(Hammerschlag, Gutowsky, Gallagher, Matich, & Cooke, 2017). Despite rare-species dives only generating ~18% of the revenue of shark-dive tourism in The Bahamas, the importance of this income is greater in economically depauperate Family Islands where these interactions take place.…”
mentioning
confidence: 99%